Epidemiologic features of deaths from influenza A (H1N1) 2009 in EsSalud insured population-2009 - Soto-Barba, Marco (2009)
To determine deaths from influenza A(H1N1) 2009 epidemiological characteristics in EsSalud insured population-2009. Design: Observational, descriptive, transversal study. Setting: Peruvian Social Security - EsSalud. Participants: Persons dead due to influenza A(H1N1). Interventions: The information was collected from the Surveillance for severe acute respiratory infections and Influenza A (H1N1) associated deaths of the insured population nationwide. A database was developed and processed according to time and space persons’ epidemiological characteristics and considering clinical features like risk factors and associated comorbidities. Main outcome measures: Deaths due to influenza A(H1N1). Results: A total of 74 deaths from influenza AH1N1 were notified, 54% (40) were men and 46% (34) women; age group most involved was 60 and more years with 26% of all deaths (19). Average age of death was 41 years. All dead patients were hospitalized and presented as main symptoms fever and respiratory distress; 54% (40) had comorbidity mainly cardiovascular disease, renal failure and obesity. As for provenance, most deaths were from Lima, followed by Arequipa and Cusco. Conclusions: Deaths by influenza A (H1N1) 2009 features in EsSalud insured patients were similar to the national trend in terms of sex distribution. There was difference in the age group with most deaths; the national age group was 50 to 59 years (18,2%) and for EsSalud 60 to more years (26%). Comorbidity in those who died in EsSalud (54%) was lower than that reported by Minsa at the national level (77,6%).